2022
DOI: 10.1371/journal.pone.0279731
|View full text |Cite
|
Sign up to set email alerts
|

High baseline body mass index predicts recovery of CD4+ T lymphocytes for HIV/AIDS patients receiving long-term antiviral therapy

Abstract: The relationship between baseline BMI and CD4+ T cells during follow-up in HIV patients in China requires further evaluation. We conducted a retrospective cohort study based on adult AIDS patients who underwent or received antiretroviral therapy from 2003 to 2019 in Guangxi, China. BMI was divided into categories and compared, and after adjusting for BMI being related to the change in CD4 lymphocyte count, with normal weight as the reference group, the BMI before treatment was positively correlated with the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…32 BMI is an indicator for assessing nutritional status, which can be a predictor of immune status in HIV patients. 33 A study in China proved that HIV patients with higher baseline BMI had a better immune recovery process. 34…”
Section: Hiv Patients Characteristicsmentioning
confidence: 99%
“…32 BMI is an indicator for assessing nutritional status, which can be a predictor of immune status in HIV patients. 33 A study in China proved that HIV patients with higher baseline BMI had a better immune recovery process. 34…”
Section: Hiv Patients Characteristicsmentioning
confidence: 99%
“…In addition, host metabolic level and genetic factors play a role in immune reconstitution. Studies ( Zhu et al, 2022 ) have demonstrated that PLHIV had better immune reconstitution with a higher baseline BMI. This may be due to the fact that leptin has higher levels in people with a higher BMI.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 99%